Potential clinical implications of HPV status and expressions of p53 and cyclin D1 among oropharyngeal cancer patients. (27th September 2018) - Lu, X. J. David; Liu, Kelly Y. P.; Soares, Rosilene C.; Thomson, Thomas; Prisman, Eitan; Wu, Jonn; Poh, Catherine F.
Abstract : Background: There is increasing evidence that high‐risk human papillomavirus plays significant role in oropharyngeal cancer; however, there is lack of knowledge on the interplay between the virus and its downstream‐related molecules and their possible prognostic values. The objectives of the study are to better understand the interplay of the HR‐HPV and its associated downstream molecules and to evaluate potential biomarkers for patient outcomes. Methods: We conducted a retrospective study with available formalin‐fixed, paraffin‐embedded tissue from 244 oropharyngeal cancer patients that received curative radiotherapy or concurrent chemoradiotherapy from 2000 to 2008. In addition to chart review, we performed HPV DNA and RNA in situ hybridization and immunohistochemistry for p53, the retinoblastoma protein, p16, and cyclin D1 analysis. Cox proportional hazard and Kaplan‐Meier survival analysis were used to determine the prognostic markers for clinical outcomes. Results: Patients averaged 57.3 ± 9.4 year‐old and were mostly males (76.2%) and ever‐smokers (76.2%). All patients received curative radiotherapy, and 44.3% received concurrent chemoradiotherapy. We detected the human papillomavirus in 77.9% of study patients. Ever‐smokers, more advanced tumor stage, and receiving radiotherapy only had poorer 5‐year overall survival, disease‐specific survival, and loco‐regional recurrence. Cases with positive human papillomavirus and p53 overexpression had poorer disease‐specific survival. Cases without human papillomavirus, but cyclin D1 overexpression, were associated with poorer 5‐year overall survival. Conclusions: Our data suggest that additional p53 and cyclin D1 testing may benefit oropharyngeal cancer patients with known human papillomavirus status.